(untitled) (Research, Society and Development, 2020)
The objective was to identify the strategies of nurse managers for the prevention and control of infections related to health care. For this, an integrative review was carried out, using the SCOPUS, BDENF, CINAHL and LILACS databases. Based on the criteria and inclusion and exclusion, there were seven publications, which were analyzed according to the level of evidence and the Critical Appraisal Skills Program tool. It was possible to identify three strategies most used by nurses: surveillance, the creation of standard operating procedures / normative instruments and permanent education. The involvement of nurses in the process of preventing and controlling infections was verified, consolidating professional performance and strengthening the importance of defining professional attributions for qualified health care.